A system level approach to estimate maximum load steps that can be applied on a fuel cell powered marine DC system. (November 2021) - Haxhiu, Arber; Chan, Ricky; Kanerva, Sami; Kyyrä, Jorma
Abstract: This paper presents a system level approach to estimate the maximum load steps on a hydrogen fuel cell powered marine system. In the proposed approach, a model has been developed to predict the system distribution voltage drop due to sudden load changes applied on the system. The estimated voltage drop is used as a metric to determine if a system can sustain the applied load change. Such technique is beneficial for system engineers in the early stage of marine system design and dimensioning. Additionally, the model can be used by a power management system to coordinate starting and stopping of fuel cells for improved system performance. In this work, the proposed approach is validated using a real-time hardware-in-loop simulation platform and it is demonstrated that the proposed approach is accurate within 1.2%.